Penguatan Pemahaman Dasar Kimia Organik melalui Pembelajaran Materi Senyawa Hidrokarbon bagi Siswa SMKN 1 Analis Kimia Gorontalo - Bialangi, Nurhayati; Arviani, Arviani; Kilo, Ahmad Kadir (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
Strengthening fundamental concepts in organic chemistry is crucial for students' academic and industrial success. This activity aimed to deepen students' understanding of hydrocarbons, including alkanes, alkenes, and alkynes, along with their physical and chemical properties. The activity also introduced key reactions such as combustion and substitution. Through this, students learned to identify molecular structures, nomenclature, and chemical properties of hydrocarbon compounds. The teaching methods used included lectures, simulations, group discussions, laboratory practices, and assessments through tests and quizzes. Discussions helped students clarify challenging concepts like the structural differences among hydrocarbons and their associated reactions. Emphasis was placed on laboratory work to ensure that students not only grasped theoretical concepts but also gained practical skills in handling chemicals, laboratory equipment, and following safety protocols. Results from the activity showed that this approach effectively enhanced both understanding and technical abilities. Students observed the unique properties and reactivity of hydrocarbons in controlled laboratory settings, which also encouraged the development of analytical and critical thinking skills. This initiative strengthened their foundation in organic chemistry and prepared them for future challenges in the chemical industry. The combination of hands-on practices and in-depth discussions proved effective in improving students' comprehension of hydrocarbons and their chemical behavior. Furthermore, it laid the groundwork for further learning about hydrocarbon derivatives and their diverse industrial applications.